Cosmopolitan Canvases: The Globalization of Markets for Contemporary Art - Olav Velthusis (ed.); Stefano Baia Curioni (ed.) (New York : Oxford University Press, 2015)
Annotation
Keywords: Art Contemporary Period; Arts